Effects of Dietary Inclusion Level of Distillers’ Dried Grains with Solubles (DDGS) from Wheat and Corn on Amino Acid Digestibilities in Broilers - Abdel-Raheem , Sherief M.; Leitgeb, R.; Iben, C. (International Journal of Poultry Science, 2011)
The objective of this study was to determine the effect of different levels of Distillers’ Dried Grains with Solubles (DDGS) from wheat and corn on prececal Amino Acids (AA) digestibilities, growth performance and some slaughter characteristics of broilers. A total number of 240 one day-chicks (Ross 308) were randomly allotted to 3 treatments (80 birds/group), with four replicate pens per treatment and 20 birds per pen. Chicks were fed the experimental diets with DDGS at levels of 0, 6 and 12%. All chicks had free access to feed and water ad libitum during the 5-wk experiment. Average daily gain, feed intake and feed conversion efficiency were determined weekly for 35 days. The results indicated that, body weight decreased in broilers fed 12 % DDGS than the control group at the end of the experiment. No significant differences with respect to feed intake and feed conversion at the first (1-22 d) and second (22-35 d) growing periods. A significant reduction in the warm and cold carcass weight and the warm and cold dressing % at 12 % inclusion level of DDGS. Tryptophan digestibility was lower (p<0.05) with the addition of 12% levels of DDGS at d 21. At day 35 there is a significant decrease in the digestibility of total amino acids, some individual AA like threonine (9.1%) and arginine (6.38%) at 12% inclusion of DDGS in comparison with the control group. The results suggest that 12 % level of DDGS from wheat and corn reduce growth performance, carcass traits, some AA and DM digestibilities in broilers under present experimental conditions.